A case for an online based business for African print material operated in Gauteng - Sibiya, Praise-God (My University, 2018)
The paper presents a business case to determine the commercial value and the viability of establishing and running an online store for the sale of African print material and other traditional accessories. Although the business case will be operated in the Gauteng Province in South Africa, its customers will not be limited to any geographical location and will thus include customers from all the provinces in South Africa including the Gauteng Province, and tourists visiting South Africa. The current market appears to be made up of informal sales points at disproportionately situated business areas in Gauteng; including “Kwa-Mai Mai”, the Fashion District, along Diagonal street in the Johannesburg CBD, and in other informal markets in major business districts such as Marabastad in Pretoria (EAU, 2012). These are the business hubs for African print material (Akinwumi, 2008). They are considered unsafe and congested, they do not respond well to consumer behavior and are managed informally rather than competitively, contrary to retail market approach expectations (Bénit-Gbaffou, 2014). African print material has been used by Africans to serve different purposes, particularly African traditional events. This fabric has also found its way into mainstream fashion, were celebrities such as Beyoncé Knowles, Rihanna, Fergie and Kim Kardashian have also taken a liking to the fabric. The emerging middle class in South Africa on the other hand has increased its spending on technological goods. The advent of social media and online shopping has also created opportunities for new entrepreneurial initiatives. This study thus presents a business case to determine the commercial value and the viability of establishing and running an online store for the sale of African print material and other traditional accessories. The results of the study conducted as part of this business case found that the online business case for the sale of African print material does have a significant and sufficient market size. This was based on the willingness and capability of potential consumers. The study also found that most effective market entry strategy is a focused differentiation strategy where value for the consumer will be increased to justify a high selling price for the business case. This will be done while simultaneously keeping cost low and by forming alliances. The most effective value chain and organizational structure for the sourcing, production and distribution therefore is one of outsourcing the modular system of production while distributing through the use of a private courier respectively. Using the Capital Asset Pricing Model as a basis, the study also Page 3 of 46 calculated a positive Net Present Value over a three year horizon which was consistent with the entry strategy findings, demonstrating a financially viable business case.
MBA
Keywords: Electronic commerce.